Strength training to improve walking after stroke: how physiotherapist, patient and workplace factors influence exercise prescription. (2nd September 2022) - Tole, Genevieve; Raymond, Melissa J.; Williams, Gavin; Clark, Ross A.; Holland, Anne E.
ABSTRACT: Background: Muscle weakness is well established as the primary impairment that affects walking after stroke and strength training is an effective intervention to improve this muscle weakness. Observation of clinical practice however has highlighted an evidence-practice gap in the implementation of evidence-based strength training guidelines. Objective : To explore perceived barriers and facilitators that influence Australian physiotherapy practices when prescribing strength training with stroke survivors undergoing gait rehabilitation. Methods : Semi-structured interviews were conducted with a convenience sample of physiotherapists currently providing rehabilitation services to patients following stroke in Australia. Interviews were transcribed verbatim and line-by-line thematic analysis was undertaken to create themes and sub-themes. Results : Participants were 16 physiotherapists (12 females) with 3 months – 42 years experience working with people after stroke. Major themes identified were1) patient factors influence the approach to strength training; 2) interpretation and implementation of strength training principles is diverse; and 3) workplace context affects the treatment delivered. Physiotherapists displayed wide variation in their knowledge, interpretation and implementation of strength training principles and strength training exercise prescription was seldom evidence or guideline based. Workplace factors included the clinical preference of colleagues, and the need to modify practice to align with workforce resources. Conclusions : Implementation of strength training to improve walking after stroke was diverse. Therapist-related barriers to the implementation of effective strength training programs highlight the need for improved knowledge, training and research engagement. Limited resourcing demonstrates the need for organizational prioritization of stroke education and skill development. Narrowing the evidence-practice gap remains a challenge.